ANTIBACTERIAL ACTIVITY AND BIOAUTOGRAPHIC EVALUATION OF EXTRACT AND FRACTION FROM TAMOENJU (HIBISCUS SURATTENSIS L.) LEAVES - YULIET; KHUMAIDI, AKHMAD; HIKMA, NUR; NURINAYAH (International Journal of Applied Pharmaceutics, 2022)
Objective: The tamoenju (Hibiscus surattensis L.) is one of the plants as traditional medicines to treat infections. Tamoenju leaves contain alkaloids, flavonoids, saponins, tannins, and steroids, a potential antibacterial agent. This study aimed to determine the antibacterial activity of tamoenju leaves extract and fraction against Staphylococcus aureus (ATCC 25923) and Salmonella typhi (ATCC 14028), and detect the active compounds using Thin Layer Chromatography (TLC) Bioautography techniques. Methods: The sample was extracted using maceration method with 96% ethanol as solvent. Fractionation of ethanol extract using the liquid-liquid extraction method using n-hexane and ethyl acetate. The agar well diffusion method was used to evaluate the antibacterial activity with various concentrations of 2.5%, 5%, 10%, and 20%, followed by TLC bioautography using n-butanol: acetic acid: aquadest (4:1:1) as the mobile phase and silica gel GF 254 as the stationary phase on the most active fraction. Zones of inhibition showed the sensitivity of the tested microorganisms. Results: The results showed the extract, n-hexane, and water fractions were more sensitive to S. typhi, while the ethyl acetate fraction was more sensitive to both bacteria. The zone of inhibition increased with the increasing extract and fractions concentration. The bioautography TLC showed that the compounds that had the potential as antibacterial in the most active fraction (ethyl acetate fraction) were flavonoids. Conclusion: The extract and fraction of tamoenju leaves have antibacterial activity. Ethyl acetate fraction had the highest antibacterial activity. The compounds predicted to have antibacterial activity against the two tested bacteria were flavonoids.